Kontribusi Sektor Perikanan Dalam Pembangunan Wilayah Kabupaten Sumedang - Tarigan, Aginta Primana; Gumilar, Iwang; Nurhayati, Atikah; Maulina, Ine (Universitas Galuh, 2025)
This study aims to analyze the contribution of the fisheries sector as a leading sector in the regional development of Sumedang Regency and to examine the strengths of the basic and non-basic sectors of fisheries in regional development in Sumedang Regency. The research method used is a quantitative method. The study was conducted using a survey method, The data collection and research were conducted from March 2024 to July 2024. The types of data used are primary and secondary data. Primary data were obtained from interviews with the Regional Government of Sumedang Regency. Secondary data were obtained from the Central Statistics Agency of Sumedang Regency, the Agriculture, Livestock, and Fisheries Office of Sumedang Regency, as well as other related agencies or institutions. These secondary data were sourced from various origins, processed from the original sources, and presented in a specific format. The necessary data include cross-section secondary data indicating specific time points and also time series data on fisheries from 2019 to 2023. The sampling technique to be used is purposive sampling. The data analysis method used is the Location Quotient (LQ) analysis. The results of the Location Quotient (LQ) analysis show that the fisheries sector in Sumedang Regency has sub-districts that serve as base areas in the aquaculture, capture fisheries, and fish processing sectors. These results prove that Sumedang Regency can meet its own regional needs and also fulfill demands from other areas. Regional development in Sumedang Regency can be maximized by enhancing development in the fisheries sector as a base sector, prioritizing it as a key investment area for regional development.